Megametaphor as a coherence and cohesion device in a cycle of literary texts - Rezanova, Zoya; Shilyaev, Konstantin (Lingua Posnaniensis, 2015)
The present study is concerned with the notion of megametaphor and its role in the cohesion and coherence of the text, as well as its intertextual function. We discuss the method of identifying and structuring megametaphor in a literary text and apply it to four novels by Jack London that have dogs as their protagonists. The megametaphor DOG IS A MAN is shown to organize the texts both conceptually - via a coherent set of frame structures of the source domain - and linguistically, by way of applying a network of metaphorical lexemes to the description of a dog.